2006
DOI: 10.1158/1535-7163.mct-06-0055
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent inhibition of human colon cancer cell growth and of prosurvival pathways by oxaliplatin in combination with ZD6474 (Zactima), an inhibitor of VEGFR and EGFR tyrosine kinases

Abstract: To date, clinical studies combining the new generation of targeted therapies and chemotherapy have had mixed results. Preclinical studies can be used to identify potential antagonism/synergy between certain agents, with the potential to predict the most efficacious combinations for further investigation in the clinical setting. In this study, we investigated the sequence-dependent interactions of ZD6474 with oxaliplatin in two human colon cell lines in vitro. We evaluated the in vitro antitumor activity of ZD6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
3

Year Published

2007
2007
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 44 publications
1
34
3
Order By: Relevance
“…However, ZD6474 does not modulate chemosensitivity in parental chemosensitive cells. These results seem inconsistent with previous reports (Morelli et al, 2005;Troiani et al, 2006) and the mechanisms underlying this difference are currently unclear. However, it is noted in these previous reports that the ZD6474 treatment schedule is the key aspect for its combination effect with cytotoxic agents.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, ZD6474 does not modulate chemosensitivity in parental chemosensitive cells. These results seem inconsistent with previous reports (Morelli et al, 2005;Troiani et al, 2006) and the mechanisms underlying this difference are currently unclear. However, it is noted in these previous reports that the ZD6474 treatment schedule is the key aspect for its combination effect with cytotoxic agents.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, an antagonistic effect was observed when cells were pretreated with ZD6474 followed by cytotoxic agents. On the contrary, a synergistic effect was evident when cells were pretreated with cytotoxic agents prior to EGFR antagonists (Morelli et al, 2005;Troiani et al, 2006). In this study, we treated MCF-7 cells with ZD6474 and cytotoxic agents simultaneously.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, we and other groups have shown that the combination of cytotoxic drugs and anti-EGFR or VEGFR-2 agents caused different antiproliferative effects in vitro depending on the treatment schedule (25,26). In this context, our group has shown that vandetanib possesses antiproliferative antitumor activity in vitro, which acts in a sequence-dependent manner with chemotherapeutic agents, such as oxaliplatin and irinotecan, in two human colon cancer cell lines (27). 5 In that study, treatment with chemotherapeutic agents followed by vandetanib resulted in enhanced antitumor activity in vitro.…”
mentioning
confidence: 85%
“…It has been very reported that oxaliplatin has synergistic effects in combination with ZD6474 (Zactima), an inhibitor of vascular endothelial growth factor receptor (VEGFR), epidermal growth factor receptor (EGFR) and RET tyrosine kinase activity. In fact, ZD6474 in combination with oxaliplatin is synergistic when oxaliplatin is administered before ZD6474 in colorectal cancer cells in vitro (19). Furthermore, combined exposure to ZD1839 (Iressa), a novel EGFR tyrosine kinase inhibitor and oxaliplatin also exerted synergy in colorectal cancer cell lines (20).…”
Section: Introductionmentioning
confidence: 99%